Enhanced non-bias-field magnetoelectric response with high detectivity in a sensing system based on electret film and magnetostrictive material. (15th February 2023) - Zhou, Yun; Yang, Siyu; Yi, Yongjie; Lan, Cheng; Wang, Jianfeng; Xu, Long
Highlights: A magnetoelectric sensing system combined by an electret thin film and a magnetostrictive rod. A significant magnetoelectric response was observed under a zero bias magnetic field. The maximum tunability of the magnetoelectric voltage coefficient was 99.8% The limit of detection of the AC magnetic field was 0.016 Oe. Abstract: An electret film and a magnetostrictive rod were used to combine a magnetoelectric sensing system. The dynamic magnetoelectric measurement was used to investigate the voltage output of the combined system. A significant non-bias-field magnetoelectric response was observed. The capacitance and magnetoelectric voltage coefficient were significantly affected by the AC and DC magnetic field. The ME voltage coefficient exhibited a step decrease with an increase in the DC field. The maximum tunability of the magnetoelectric voltage coefficient was 99.8%. The limit of detection of the AC magnetic field decreased rapidly with a very high value at lower frequencies and decreased slowly with a very low value at higher frequencies. The minimum value of the limit of detection was approximately 0.016 Oe. These findings indicated the combination for potential applications in magnetic detectors, magnetoelectric sensors, switches, and energy converters.